An examination of the effect of macroeconomic variables on Ghana stock market returns in Ghana - Tieku, Elizabeth (2016)
A thesis submitted to The Department of Economics, Kwame Nkrumah University of Science and Technology in partial fulfilment for the award of a degree of Master of Science (Economics).